The Application of Indigo Strobilanthes Cusia Natural Dye Paste using Block Printing Technique on Textile - Darusiam, Hasna Maritza; Ramadhan, Mochammad Sigit; Takao, Gina Shobiro (Humaniora: Journal of Indonesia Culture and Society, 2025)
Natural dyes can promote environmental sustainability while offering a unique and attractive aesthetic. This approach enhances the appeal of textile products, adding value and creating a competitive advantage in the creative and fashion industries. Indigo from Strobilanthes cusia is a well-known natural dye primarily used by textile artisans and designers to create vibrant indigo-colored fabrics. In surface textile design, there is potential to modify indigo solutions into a paste, which can be used to create motifs on fabric through block printing techniques. The research aims to develop an optimal indigo paste formula for block printing and to examine the application of natural dyes on fabric. The research employs a mixed-methods approach, collecting data from literature reviews, direct observations, social media analysis, and experimental work. During the experimental phase, block printing techniques are applied using different paste formulas on various fabric types to assess the optimal viscosity and fixation methods of the paste. The findings indicate that the natural dye derived from the indigo paste of Strobilanthes cusia yields an effective formula for block printing, particularly in terms of motif sharpness and color durability. The optimal composition was found to be 10 g of paste mixed with 5 mL of water, resulting in a viscosity value of 191 mPa·s. These findings can inspire the development of more sustainable textile products and expand the use of natural dyes across various textile printing techniques, potentially leading to innovative fashion products.